The Role of COBIT5 as a Reference for Quality Service Quality Improvement - Kevin Pratama Arthananda; Wella Wella (Universitas Multimedia Nusantara, 2021)
Bank Central Asia Tbk. is the largest private bank company in Indonesia, which is now owned by one of the largest cigarette group companies in the world, namely Djarum. PT. Bank Central Asia Tbk. make various efforts to improve the quality of service quality by setting a standard and policy. One of them is the determination of ITIL V3 standardization, which covers the entire IT Service process. ITIL V3 is a series of concepts and techniques for infrastructure management, development, and information technology operations. These efforts were made to meet the ISO 20000 standardization to obtain ISO 20000 certification in 2011. However, PT Bank Central Asia Tbk wants to continue to improve the quality of IT services for the better, therefore PT Bank Central Asia Tbk. chose to use the COBIT 5 framework as a method of measuring the quality of IT service quality, especially in the field of IT Service Management (ITSM) in the DSS02 (Manage Service requests and Incidents) and DSS03 (Manage Problems) processes. The result of this research is that the Capability Level of the DSS02 and DSS03 processes is known at PT Bank Central Asia Tbk. the current condition is level 3 (Established Process), while the target level to be achieved is level 4 (Predictable Process). So that to reach the next level, PT Bank Central Asia is expected to have followed the recommendations for improvement given.